2021
DOI: 10.1111/gbi.12472
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis of microbial communities across a transect from low to highly hydrocarbon‐contaminated soils in King George Island, Maritime Antarctica

Abstract: Soil samples from a transect from low to highly hydrocarbon-contaminated soils were collected around the Brazilian Antarctic Station Comandante Ferraz (EACF), located at King George Island, Antarctica. Quantitative PCR (qPCR) analysis of bacterial 16S rRNA genes, 16S rRNA gene (iTag), and shotgun metagenomic sequencing were used to characterize microbial community structure and the potential for petroleum degradation by indigenous microbes. Hydrocarbon contamination did not affect bacterial abundance in EACF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
(66 reference statements)
1
5
0
1
Order By: Relevance
“…These bacteria groups known to be involved in nitrogen fixation 42 . These results are in consistent with other studies that observed dominance of Proteobacteria in agricultural soils 43,44 . Upon treatment with MONPs, there was no change in the abundance of Proteobacteria while Bacteriodetes generally increased after 30 days of exposure.…”
Section: Discussionsupporting
confidence: 94%
“…These bacteria groups known to be involved in nitrogen fixation 42 . These results are in consistent with other studies that observed dominance of Proteobacteria in agricultural soils 43,44 . Upon treatment with MONPs, there was no change in the abundance of Proteobacteria while Bacteriodetes generally increased after 30 days of exposure.…”
Section: Discussionsupporting
confidence: 94%
“…4 ). Proteobacteria and Actinobacteria have been reported to be the most abundant phyla in both Antarctic soils 34 and soils contaminated with PAHs 35 . Figure 5 a,b show all the genera belonging to the Proteobacteria and Actinobacteria phyla, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sulbaran-Bracho et al 6 determined the community composition of bacteria during diesel biodegradation by consortium LR-10 isolated from Antarctic rhizosphere soil and found that the dominant bacterial genera were Pseudomonas , Candidimonas , Rhodanobacter , Renibacterium , Pseudoarthrobacter , and Frateuria . Jurelevicius et al 35 investigated the microbial communities present in hydrocarbon-contaminated soils from King George Island, Antarctica. They found positive correlations between the abundances of Cytophaga , Methyloversatilis , Polaromonas , and Williamsia and the concentrations of total petroleum hydrocarbons and/or PAHs.…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomic analysis is a valuable tool for environmental monitoring, enabling comprehensive identification of microbial communities in specific habitats ( Feng et al, 2018 ; Jurelevicius et al, 2022 ). In this study, bacterial communities in sediment samples were analyzed using amplicon NGS targeting the V3 and V4 regions of the 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%